Psychopathologie et poétique de l’« ennui » en France au xixe siècle - Juan Rigoli (Criminocorpus)
At the turn of the 19th century, « weariness » (ennui) acquires, or rather recovers, the meaning of a subjective and painful experience in a strong sense, understood in terms of a void. It figures at the center of the psychiatric nosography of suicide, while denoting, for Chateaubriand and Senancour, an essential element of romantic consciousness and esthetics. A vast spectrum of common and scholarly terms, absolute or partial substitutes for « weariness », determines the narratives and descriptions of the melancholic state, with which it is associated. Through terms such as « disgust of life », « spleen », « vague passions », « tædium vitae » (in the Senecan sense), « misopsychia », among others, the boundary between literature and medicine is at once formed and blurred. An uncertain entity is incorporated into psychopathology, one that is regularly defended and contested, from Esquirol to Minkowski, and which awakens the memory of a poetics from which it believed to have freed itself.